2005
DOI: 10.1093/bja/aei157
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography for ilioinguinal/iliohypogastric nerve blocks in children † †This study was performed at the Red Cross Children Hospital, Klipfontein Road, Rondebosch 7700, Cape Town, South Africa.

Abstract: Ultrasound-guided ilioinguinal/iliohypogastric nerve blocks can be achieved with significantly smaller volumes of local anaesthetics. The intra- and postoperative requirements for additional analgesia are significantly lower than with the conventional method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 321 publications
(43 citation statements)
references
References 14 publications
0
42
1
Order By: Relevance
“…Although not directly applicable to our results, we explored for other studies on the possible use of US-INB in children. Apart from Willschke and colleagues [4], we only found 4 others. Two of them looked at the exact site of injection and plasma levels of ropivacaine, respectively [46, 47].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Although not directly applicable to our results, we explored for other studies on the possible use of US-INB in children. Apart from Willschke and colleagues [4], we only found 4 others. Two of them looked at the exact site of injection and plasma levels of ropivacaine, respectively [46, 47].…”
Section: Discussionmentioning
confidence: 87%
“…The use of US could potentially improve the precision of both CB and INB. It has been shown that the success rate of caudal injection [44, 45], as well as INB [4], could be better using US guidance. Despite this, we only found 2 studies comparing US-INB to CB [8, 29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL/IH blocks were performed based only on landmarks in this study and in 86% of the blocks, the local anesthetic was found to be incorrectly administered in adjacent anatomic structures instead of around the IL/IH nerves [70]. Another study in children demonstrated that IL/IH nerve blocks can be successfully achieved with significantly smaller volumes of local anesthetic with the use of ultrasound over the landmark-based approach and that intra-and postoperative analgesic requirements are lower with the ultrasound-guided block [71].…”
Section: Clinical Evidencementioning
confidence: 66%